Оптимізація електрохімічної технології перероблення вольфрамвмісних псевдосплавів - Єрмоленко, Ірина Юріївна; Ведь, Марина Віталіївна; Сахненко, Микола Дмитрович; Андрощук, Дмитро Степанович (НТУ "ХПІ", 2012)
It is shown, that the use of polyligand electrolyte and pulsed mode for the anodic dissolution of tungsten pseudo alloys ensure the efficiency and selectivity of the process. The optimum composition of the electrolyte and the electrolysis parameters for the intensification of the tungsten recycling were determined.
Keywords: вольфрам; кусковий брухт; вольфрамова проволока; тверді сплави; електроліти; електроліз; кобальт; окиснення; анодне розчинення